A Legal Review of Indonesia’s Nickel Ore Export Ban Policy in the Context of Economic Value Addition and Industrial Growth - Thio, Herman; Lie, Gunardi (Jurnal Pembaharuan Hukum, 2025)
Indonesia implemented a nickel ore export ban as part of its mineral downstreaming policy to increase domestic value added, strengthen industrial development, and secure long-term economic growth through local processing and refining activities. This policy is legally grounded in Law Number 4 of 2009 as amended by Law Number 3 of 2020 on Mineral and Coal Mining, as well as Ministerial Regulation of Trade Number 96 of 2019. This study aims to examines the impact of Indonesia’s nickel ore export ban on value-added economic development and its compatibility with World Trade Organization (WTO) rules, particularly General Agreement on Tariffs and Trade (GATT) 1994 Article XI:1 and Article XX. The research employs a normative legal research method using qualitative analysis of legal instruments, WTO dispute rulings, and relevant literature. The findings show that the export ban has encouraged investment in smelters, increased downstream industrial capacity, and supported strategic sectors such as electric vehicle batteries. However, the WTO found the policy violated with GATT Article XI:1 and unjustified under Article XX exceptions. While Indonesia’s policy successfully promotes domestic value addition, it also demonstrates the need to align national resource-based industrial policies with international trade obligations to ensure sustainable and legally compliant economic development.